ICE CREAM SERBAT JAHE: INOVASI ES KRIM SEHAT SEBAGAI UPAYA PELESTARIAN MINUMAN KHAS LOMBOK DAN PENINGKATAN EKONOMI MASYARAKAT LOKAL (Jurnal Pepadu, 2023)
Lombok Island is one of the popular tourist destinations for both national and international communities. This potential makes various business opportunities that can be done to increase the economic income of its citizens. Businesses that prioritise the distinctiveness of a region also have a great opportunity to become a source of economic improvement for the community. Ginger sherbet is a well-known local cultural heritage of West Lombok. Ginger â€œSerbatâ€ is a drink made from a blend of red ginger, white ginger, lemongrass, cinnamon and chilli bunches. The natural ingredients, which are rich in bioactive components, make this drink very good for consumption. However, the consumption of ginger â€œSerbatâ€ is currently limited to the elderly. Innovation in making â€œSerbatâ€ products into ice cream can be done to reach all groups. New products in the form of ginger â€œserbatâ€ ice cream can be developed in areas that are busy with tourism. The development of the West Lombok region, especially the Senggigi area and its surroundings, has long been the main centre of tourism on the island of Lombok. However, there are not many local food craftsmen who can attract tourists. Training in making ginger â€œserbatâ€ was given to women in the Batu Layar, Meninting area around Senggigi. The additional skills are expected to be a business opportunity that they can further develop to increase their income.